Editor’s Letter - Lampón, Jesús F. (Mercados y Negocios, 2023)
What is a high-impact factor journal? Is it essential to publish in high-impact journals? These questions repeatedly arise in academic conversations, congresses, and workshops, and, indeed, they are relevant.